3D Hybrid Plasmonic Framework with Au Nanopillars Embedded in Nitride Multilayers Integrated on Si. Issue 17 (23rd June 2020) - Huang, Jijie; Wang, Xuejing; Li, Dongfang; Jin, Tiening; Lu, Ping; Zhang, Di; Lin, Pao‐Tai; Chen, Hou‐Tong; Narayan, Jagdish; Zhang, Xinghang; Wang, Haiyan
Abstract: Integration of nanoscale photonic and plasmonic components on Si substrates is a critical step toward Si‐based integrated nanophotonic devices. In this work, a set of unique complex 3D metamaterials with intercalated nanolayered and nanopillar structures with tunable plasmonic and optical properties on Si substrates is designed. More specifically, the 3D metamaterials combine metal (Au) nanopillars and alternating metal‐nitride (Au‐TiN and Au‐TaN) nanolayers, epitaxially grown on Si substrates. The ultrafine Au nanopillars ( d ≈ 3 nm) continuously grow throughout all the nanolayers with high epitaxial quality. Novel optical properties, such as highly anisotropic optical property, high absorbance covering the entire visible spectrum regime, and hyperbolic property in the visible regime, are demonstrated. Furthermore, a waveguide based on a silicon nitride (Si3 N4 ) ridge with a multilayer structure is successfully fabricated. The demonstration of 3D nanoscale metamaterial design integrated on Si opens up a new route toward tunable metamaterials nanostructure designs with versatile material selection for various optical components in Si integrated photonics. Abstract : A set of unique complex 3D metamaterials with intercalated nanolayered and nanopillar structures are fabricated on Si substrates. Novel optical properties, such as highly anisotropic optical property and hyperbolic property in the visible regime, are demonstrated. Furthermore, a waveguide based on a silicon nitride (Si3 N4 ) ridge with a multilayer structure is successfully fabricated.